Desensitization Outcomes: Quantifying and Questioning. Issue 7 (9th June 2014) - Cole, E.; Tinckam, K. J.
<x xml:space="preserve">Abstract</x> In the article by Orandi et al (page 1573), the large cohort of desensitized renal transplant recipients offers an important opportunity for long‐term outcome comparisons with patients on dialysis awaiting compatible allografts, and it should stimulate efforts to improve accuracy, precision, and standardization of antibody testing.